Settling down with anthropomorphic clay figurines in eastern North America - Miller, G. Logan (Frontiers in Human Dynamics, 2024)
Indigenous peoples have occupied eastern North America for well over 10,000 years yet the earliest anthropomorphic figurines were only manufactured in the past several thousand years. This emergence of human figurine traditions in eastern North America is correlated with increased settlement permanence and community size related to key demographic thresholds. In this paper, I present an overview of two previously unreported figurine assemblages from the Middle Woodland period in Illinois and use these as a jumping off point to examine the emergence of early human figurines in eastern North America. To illustrate the importance of the correlation between anthropomorphic figurines and settling down, I focus on what figurines do that encouraged the emergence of widespread traditions of figurine manufacture and use as the size of affiliative communities increased. This involves examining early figurines, and their broader context, through the lens of a model of the socioeconomic dynamics of settling down in conjunction with an examination of the materiality of miniature 3-D anthropomorphic figurines. Key to this latter perspective is understanding not what figurines represent but what they do.